Epistemologi Tafsir Klasik: Studi Analisis Pemikiran Ibnu Katsir - Wely Dozan (FALASIFA : Jurnal Studi Keislaman, 2019)
Epistemology is basically a branch of philosophy that studies the roots of thought and basic concepts of submission. The concept has a paradigm that gives birth to an idea in the process of thinking. This shows that there is an epistemology used by classical commentators, Ibn Katsir in understanding and explaining verses of the Qur'an in a lengthy and broad manner. Because of this interpretation if examined and critically examined again will be found in a comprehensive direction of thought in interpreting the Qur'an. Therefore, this paper is here to express and map significantly the epistemology of Ibn Katsir thought in the interpretation process. Thus it can be concluded, the source of knowledge in the interpretation contains two broad classifications, namely: First. Tafsir Bil Ma’tsur. Secondly, Tafsir Al-Ra'yi. The interpretation of bil matsur is divided into four interpretations, namely, the interpretation of the Qur’an with the Qur’ran, the interpretation of the Qur’an with the Hadith, the interpretation of the Qur’an with friends, and the interpretation of the Qur’an with the opinion the tabi'in. while the interpretation of Al-Ra'yi as rational is supported by the science of the rules of language to reveal the meaning of sitematic ceremony. In short, the author will make a clear contribution on how the epistemology of the Qur'anic interpretation is carried out by Ibn Katsir.